Evolution of the Uzbek National Guard: From Paramilitary Origins to an Independent Ministry - Shamsieva, Makhfuzakhon (International Journal of Contemporary Sciences (IJCS), 2024)
The Uzbek National Guard has evolved significantly since its inception as a paramilitary unit to become a fully-fledged independent ministry. This transformation was facilitated by legal reforms, organizational advancements, and current State Administration’s strategic vision. The National Guard’s role has expanded beyond security functions to contribute to public safety and national resilience. The study also highlights the importance of psychological well-being among National Guard personnel, emphasizing the need for comprehensive support systems to address the challenges of military service. This brief communication provides a nuanced understanding of the National Guard’s historical development, obstacles, and innovative strategies, offering valuable insights into the dynamics of military reform and psychological support mechanisms. The Uzbek National Guard serves as a case study for global security policy and military organizational culture in the 21st century